The gift - McFadden, Freida ([United States] : [Freida McFadden], 2022)
"It s Christmas Eve and Stella Hansen is broke. She is so broke that despite working two jobs, she can t even afford a present for her husband on their first Christmas as man and wife. But then a mysterious storekeeper at a pawn shop offers Stella an intriguing trade. Stella wants more than anything to buy her husband the Christmas gift of his dreams. But will it come at a terrible price?" --
Keywords: Gifts -- Fiction; Pawnbrokers -- Fiction; Poverty -- Fiction; novellas; Christmas fiction; Fiction; Novellas; Psychological fiction; Christmas fiction; Psychological fiction; Novellas; Novellas